Is Multiple Sclerosis an Autoimmune Disease?. (16th May 2012) - Wootla, Bharath; Eriguchi, Makoto; Rodriguez, Moses
Abstract : Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS) with varied clinical presentations and heterogeneous histopathological features. The underlying immunological abnormalities in MS lead to various neurological and autoimmune manifestations. There is strong evidence that MS is, at least in part, an immune-mediated disease. There is less evidence that MS is a classical autoimmune disease, even though many authors state this in the description of the disease. We show the evidence that both supports and refutes the autoimmune hypothesis. In addition, we present an alternate hypothesis based on virus infection to explain the pathogenesis of MS.